Postsecularism as colonialism by other means - Bugyis, Eric (Critical research on religion, 2015)
The claim that we are entering a "postsecular" age supposedly marks a new openness toward public religion, which was expected to wither as societies modernized. Similarly, postcolonial theory has attempted to think through the public resurgence of indigenous culture after the collapse of "Western" political regimes, which also predicted and prescribed its privatization. Drawing on the work of Partha Chatterjee, this paper argues that the "postsecular," particularly as it is deployed by Jürgen Habermas and Alasdair MacIntyre, seeks to seduce religious believers and practitioners into just this same logic of self-colonization so that they might be recognized as defenders of an increasingly insecure, liberal nation-state against those who might seek to take advantage of its vulnerability.